Consumer Preferences towards Service Industry: A Factorial Study of Restaurants - Jaiswal, Gaurav; Matharu, Manita; Sahu, Praveen (Indian Journal of Marketing, 2010)
Globalization has made drastic changes in world economy and it has offered loads of opportunities for business houses and industries-specifically hospitality services. The Restaurant industry today is a diverse composite of ownership patterns and varying management structures which offer a variety of services. However, the basic product, which is the Drink-Food, remains the same. With the emergence of weekend culture in metros, increment in standard of living of service class people, emergence of mall and retail culture, the Indian restaurant industry has a profitable future. Customers usually consider various factors before making a choice for a restaurant. These factors may be understand as service, taste, cleanliness, location, charge, payment mode, loyalty, free gifts, variety in terms of food available., brand name etc. These are the reasons due to which identification of customer preference becomes a needy element for restaurant management.